Comparing Attachment Networks During Middle Childhood in Two Contrasting Cultural Contexts - Becke, Sophia D.; Bongard, Stephan (Frontiers in Psychology, 2018)
Cultural psychology assumes that the ecocultural conditions of a particular setting shape children’s pathways, resulting in multiple adaptive solutions to universal developmental tasks. While the adaptivity of attachment and children’s psychosocial development during the early years has been thoroughly investigated, attachment research during middle childhood continues to reflect Western ideals of family. Adhering to ideas of monotropy, most studies only focus on parental attachment figures. However, this restricted empirical perspective does not only result in a Eurocentric bias, it also neglects theoretical reflections on the growing complexity of attachment during middle childhood, thus only considering a limited selection of all individuals contributing to the children’s feeling of security, even in Western settings. To investigate the variability and adaptivity of attachment during middle childhood, this study assessed children’s attachment figures in two extreme settings of development, introducing an exhaustive network perspective on attachment during this developmental stage. Children of the Cameroonian Nseh (N = 11) and German children from Bad Nauheim (N = 11) identified and differentiated all individuals contributing to their attachment need in an exploratory and transdisciplinary approach. The socio-structural composition of children’s attachment networks follows the context-specific systems of care and concepts of interconnectedness and the ecological features of each setting, resulting in marked differences between both contexts. The functional composition, however, reflects children’s preoccupation with similar developmental challenges across settings. Same-aged peers contribute to the children’s feeling of safety in both settings, thereby deviating from previous reflections on their subordinate relevance during middle childhood. Overall, these results support the adaptiveness of children’s attachment patterns while also demonstrating universal trends across contexts. They highlight the collective nature of attachment during middle childhood that exceeds the impact of individual dyads. Thus, broad and context-sensitive research strategies become a necessary addition to attachment research in order to generate an exhaustive understanding for children’s development across cultural contexts.